Feasibility and Accuracy of Transduodenal Endoscopic Ultrasound-Guided Fine-Needle Aspiration of Solid Lesions Using a 19-Gauge Flexible Needle: A Multicenter Study - Germana de Nucci; Maria Chiara Petrone; Nicola Imperatore; Edoardo Forti; Roberto Grassia; Silvia Giovanelli; Laura Ottaviani; Vincenzo Mirante; Giuseppe Sabatino; Carlo Fabbri; Mauro Manno; Paolo Giorgio Arcidiacono; et al. (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) is the go-to method for obtaining samples from gastrointestinal tract and pancreatic lesions. When the transduodenal approach is utilized, the use of a more flexible needle, such as a nitinol 19-gauge (G) needle, has been recommended. The aim of this study was to evaluate the feasibility and accuracy of 19-G flexible aspiration needles in obtaining samples from solid lesions through a transduodenal approach. Methods This was a retrospective analysis of prospectively collected data from eight Italian endoscopy centers. Consecutive patients with solid lesions who underwent transduodenal EUS-FNA with a 19-G flexible needle were included. Results A total of 201 patients were enrolled. According to histology, EUS, radiology and 12 months of follow-up, 151 patients had malignant lesions and 50 patients had benign lesions. EUS-FNA was feasible in all cases. An adequate histologic sample was obtained in all except eight cases (96.1%). The sensitivity of EUS-FNA was 92.1% (95% confidence interval [CI], 86.8%-95.7%), and the specificity was 100% (95% CI, 90.5%-100%). The positive predictive value was 100% (95% CI, 93.4%-100%), and the negative predictive value was 74% (95% CI, 62.8%-82.7%). The diagnostic accuracy was 93.5% (95% CI, 89.2%-96.5%). Conclusions The transduodenal approach for obtaining samples from solid lesions using a 19-G flexible needle seems feasible and accurate.